2021
DOI: 10.3390/ijerph182312502
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Surgical Approach of Insertion Ventilation Tubes (Tympanostomy) and Adenoidectomy in Comparison with Non-Surgical Approach (Watchful Waiting Approach) in Children at the Age between 1 and 6 and Who Suffer from Otitis Media with Effusion (OME) in 12-Month Period of Observation—The Retrospective Analysis

Abstract: (1) Background: Otitis media with effusion (OME) is one of the most common diseases in childhood. The objective was to assess clinically the effectiveness of the surgical approach (tube insertion with adenoidectomy) in comparison with the non-surgical approach (watchful waiting) during a 12-month observation period. (2) Methods: This study was retrospective and obtained approval from the bioethics committee. The criteria of inclusion in the first group (surgical approach) were: (1) a diagnosis of chronic otiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The injury to the children's ears reduces their postoperative pain, thereby significantly improving treatment safety [ 14 ]. However, some clinical studies found that the disease recurrence rate of children with secretory otitis media treated only by endoscopic tympanic membrane catheterization is still high [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The injury to the children's ears reduces their postoperative pain, thereby significantly improving treatment safety [ 14 ]. However, some clinical studies found that the disease recurrence rate of children with secretory otitis media treated only by endoscopic tympanic membrane catheterization is still high [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the non-surgical group, 10 children achieved 1 year (365 days) without recurrence, but about the same number achieved less than 30 days without recurrence, and 9 children achieved no more than 60 days without recurrence. The certainty of treatment in group 1 (surgical) was higher than in group 2 (watchful waiting), and the number of days without recurrence was also significantly higher in group 1 than in group 2 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%